A long-persistent phosphorescent chemosensor for the detection of TNP based on CaTiO3:Pr3+@SiO2 photoluminescence materials. Issue 30 (4th May 2018) - Li, Fangfang; Wang, Fengyi; Hu, Xuan; Zheng, Baozhan; Du, Juan; Xiao, Dan
Abstract : An effective and facile phosphorescence sensing approach was developed for 2, 4, 6-trinitrophenol (TNP) detection using CaTiO3 :Pr 3+ @SiO2 photoluminescence materials. Abstract : The detection of nitroaromatic explosives is important due to their strong explosive force and harmfulness in the environment, and for homeland security and public safety. Herein, a phosphorescence CaTiO3 :Pr 3+ @SiO2 nanosensor was successfully developed for the sensitive and selective detection of 2, 4, 6-trinitrophenol (TNP). The red-emitting phosphorescent chemosensor CaTiO3 :Pr 3+ @SiO2 possessed a long enough phosphorescence lifetime of 0.016 s. The TNP induced phosphorescence quenching process of CaTiO3 :Pr 3+ @SiO2 presented a wide linearity with TNP concentrations ranging from 0.5 to 100 μM, and the detection limit was found to be 20.6 nM. Furthermore, this sensor displayed a high selectivity toward TNP over other structurally similar compounds like 2, 4, 6-trinitrotoluene (TNT), 2, 4-dinitrotoluene (DNT), 4-nitrotoluene (NT), 2, 4-dinitrophenol (DNP), 4-nitrophenol (NP) and phenol. This sensing system was successfully used in the test of TNP concentrations in water samples, and showed great potential for practical application.